2016
DOI: 10.2217/pgs-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

African-Specific Variability in the Acetylcholine Muscarinic Receptor M4: Association with Cocaine and Heroin Addiction

Abstract: Cholinergic receptors' variants may contribute to drug addiction and have a potential role as pharmacogenetic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The M4Rs on D1R-expressing neurons could be interesting as pharmacological targets, as they exert control over a broad array of behaviors related to addiction pathology; including locomotor sensitization, impulsivity, drug seeking and reinstatement of drug-seeking behavior after extinction. In line with this, a recent study on genetic polymorphisms within the M4R gene revealed a link to both cocaine and heroin addiction in human subjects (Levran et al, 2016 ).…”
Section: Discussionmentioning
confidence: 75%
“…The M4Rs on D1R-expressing neurons could be interesting as pharmacological targets, as they exert control over a broad array of behaviors related to addiction pathology; including locomotor sensitization, impulsivity, drug seeking and reinstatement of drug-seeking behavior after extinction. In line with this, a recent study on genetic polymorphisms within the M4R gene revealed a link to both cocaine and heroin addiction in human subjects (Levran et al, 2016 ).…”
Section: Discussionmentioning
confidence: 75%
“…M4Rs on D1R neurons exert control over a broad array of behaviors related to addiction pathology, including locomotor sensitization, impulsivity, drug-seeking and relapse behavior after extinction. In line with this notion, a recent study on genetic polymorphisms within the M4R gene revealed a link to both cocaine and heroin addiction in human subjects (Levran et al, 2016).…”
Section: M4r Function In Learning and Motivation -Can We Really Tell?mentioning
confidence: 76%
“…Moreover, the conditional deletion of M4 receptors from D1-receptor expressing neurons leads to increased locomotor responses to psychostimulants, as well as an elevated dopamine efflux in the striatum upon amphetamine injections (Jeon et al, 2010). A recent study on genetic polymorphisms within the M4R gene revealed a link to both cocaine and heroin addiction in human subjects (Levran et al, 2016).…”
Section: The Muscarinic Acetylcholine Receptor M4mentioning
confidence: 99%
“…The sample includes subjects with opioid addiction (OD) and controls and was described in detail elsewhere 14 . Briefly, OD subjects (cases) were recruited at several opiate treatment programs in the US (e.g., Manhattan Campus of VA NY Harbor Health Care System, Weill Medical College of Cornell University, and Dr. Miriam and Sheldon G. Adelson Clinic for Drug Abuse Treatment and Research, in Las Vegas) or at the Rockefeller University.…”
Section: Methodsmentioning
confidence: 99%
“…All cases had a history of at least 1 year of multiple daily uses of heroin and were on methadone maintenance treatment at the time of recruitment. The European American (EA) sample included subjects with >50% European/Middle Eastern ancestry contributions, based on structure or PC analysis as described 14 , 15 (OD, n = 545; Controls, n = 196). The African American (AA) sample included subjects with >50% African ancestry contribution (OD, n = 308; Controls, n = 190); self-identified Hispanics were excluded.…”
Section: Methodsmentioning
confidence: 99%